Assessment of Knowledge and Practices towards Swine flu: A cross-sectional study among rural housewives - Kumari, Rashmi; Gupta, Rajiv Kumar; Langer, Bhavna; Verma, Aruna (Indian Journal of Community Health, 2016)
Background: Swine flu is an emerging public health problem in various countries including India and was declared a “Phase 6 Pandemic” by WHO in 2009. India ranks as 3rd most affected country for cases and deaths of swine flu globally. Objectives: To assess the level of knowledge and practices regarding Swine flu among rural housewives of Jammu and to find out the association between the two. Methods: A cross-sectional study was conducted during the month of April 2015 using a pre-tested and semi-structured questionnaire among 310 housewives from two villages of Jammu district. Results: Adequate knowledge was seen in 61.9% of the respondents and 53.5% had followed good practices. Mean (SD) for knowledge and practices score was 11.4(2.37) & 10.3(2.58) respectively. Literacy levels were identified as a positive predictor for adequate knowledge and good practice score. A linear relationship was evident both between knowledge / practices as well as age upto 40 years after which there was a declining trend. Also significant positive association was found between knowledge and practices (p<0.001). Conclusions: Age and education played a key role in attaining adequate knowledge and inculcating healthy practices towards prevention of swine flu. Continuous and sustained efforts are required on the part of government to impart scientific and necessary information to the target population.